SENTIDO, SINSENTIDO Y LOS SENTIDOS - Putnam, Hilary (PENSAMIENTO CONTEMPORANEO, 2000)
TRADUCCION DE: THE DEWEY LECTURES 1964: SENSE, NONSENSE AND THE SENSES: AN INQUIRY INTO THE POWERS OF THE HUMAN MIND